2009
DOI: 10.1152/ajpendo.90945.2008
|View full text |Cite
|
Sign up to set email alerts
|

Lipid and insulin infusion-induced skeletal muscle insulin resistance is likely due to metabolic feedback and not changes in IRS-1, Akt, or AS160 phosphorylation

Abstract: Hoy AJ, Brandon AE, Turner N, Watt MJ, Bruce CR, Cooney GJ, Kraegen EW. Lipid and insulin infusion-induced skeletal muscle insulin resistance is likely due to metabolic feedback and not changes in IRS-1, Akt, or AS160 phosphorylation. Am J Physiol Endocrinol Metab 297: E67-E75, 2009. First published April 14, 2009 doi:10.1152/ajpendo.90945.2008.-Type 2 diabetes is characterized by hyperlipidemia, hyperinsulinemia, and insulin resistance. The aim of this study was to investigate whether acute hyperlipidemia-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
70
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 59 publications
12
70
0
Order By: Relevance
“…These data strongly suggest that sortilin restoration, rather than signaling competency involving Akt phosphorylation, is crucial for maintaining the insulin-responsive GLUT4 recycling in skeletal muscle cells at least under the present culture conditions. In excellent agreement with this idea, it has become increasingly apparent that the most deleterious defects of skeletal muscle insulin resistance including those evoked by palmitate/high fat occur independently of the IRS signaling cascades (53,(55)(56)(57). Moreover, several lines of evidence have also demonstrated that despite its therapeutic benefits, rosiglitazone, a PPAR␥ agonist, failed to ameliorate the IRS signaling cascade defects in the skeletal muscles of FFA-induced insulin resistant rodents (58) as well as that in human patients with type 2 diabetes (59).…”
Section: Discussionmentioning
confidence: 90%
“…These data strongly suggest that sortilin restoration, rather than signaling competency involving Akt phosphorylation, is crucial for maintaining the insulin-responsive GLUT4 recycling in skeletal muscle cells at least under the present culture conditions. In excellent agreement with this idea, it has become increasingly apparent that the most deleterious defects of skeletal muscle insulin resistance including those evoked by palmitate/high fat occur independently of the IRS signaling cascades (53,(55)(56)(57). Moreover, several lines of evidence have also demonstrated that despite its therapeutic benefits, rosiglitazone, a PPAR␥ agonist, failed to ameliorate the IRS signaling cascade defects in the skeletal muscles of FFA-induced insulin resistant rodents (58) as well as that in human patients with type 2 diabetes (59).…”
Section: Discussionmentioning
confidence: 90%
“…Numerous studies have demonstrated that insulin resistance is linked with increased amounts of various deleterious lipid intermediates within skeletal muscle [1,2]. Accumulation of LCACoA in muscle has been observed in association with insulin resistance in high-fat fed rats [46] and in rats and humans infused with lipid [47,48]. LCACoA have been shown to inhibit hexokinase activity, thereby impairing glucose phosphorylation and reducing glucose uptake [49].…”
Section: Discussionmentioning
confidence: 99%
“…A relative shortage of insulin causes a delay in glucose uptake within the cells, despite a normal glucose level. Insulin resistance is also associated with the accumulation of lipid intermediates such as long chain acyl-coA, which are presumed to be toxic and responsible for metabolic derangement (Morris and Turnbull 1998;Hoy et al 2009). Thus, in case of an increase in CK, additional glucose needs to be administered.…”
Section: Glucose Infusion and Laboratory Measurementsmentioning
confidence: 99%